The establishment of a primary colon carcinoma cell line - Zubaidah Zakaria,; Gregory A.R.A.,; Tong. S,; Boon. C.F,; Asril Yusof,; Norhanom Abdul Wahab,; Latifah Saiful Yazan,; Muhammad Saifulamman Mohamed Said, (penerbit ukm, 2003)
A primary human colon carcinoma cell line (IMR22) was established in the Institute for Medical Research from a 71 years old Chinese m,an who had a right Hemicolectomy done for a fungating mass in the carcum. The tumour mass was then confirmed histopathologically to be a well differentiated Adenocarcinoma Dukes Stage II, Apiece of the tumour tissue resected fresh from the operating theatre was grown to extablish the cell line. The initial growth medium was in Amniomax C 100 supplemented with Fungizone, Penicillin and Streplomycin and was later changed to Medium 199 with Earl’s salt supplemented with 20% fetal calf serum, Kanamycin, Penicillin and Streptomycin and Lgtutamine. The IMR22 line established after ten passages with the occurrence of single type of cell in the culture whose morphological characteristics resembled that of the primary tumour.